2022
DOI: 10.3390/nu14010219
|View full text |Cite
|
Sign up to set email alerts
|

High Hydrostatic Pressure Processing of Human Milk Increases Apelin and GLP-1 Contents to Modulate Gut Contraction and Glucose Metabolism in Mice Compared to Holder Pasteurization

Abstract: Background: High hydrostatic pressure (HHP) processing is a non-thermal method proposed as an alternative to Holder pasteurization (HoP) for the sterilization of human breast milk (BM). HHP preserves numerous milk bioactive factors that are degraded by HoP, but no data are available for milk apelin and glucagon-like peptide 1 (GLP-1), two hormones implicated in the control of glucose metabolism directly and via the gut–brain axis. This study aims to determine the effects of HoP and HHP processing on apelin and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…For example, as BSSL remains active in HHP‐DM, 10 we can postulate that milk triacylglycerols and diacylglycerols can be hydrolyzed and absorbed faster and more efficiently metabolized in HHP‐DM pups. For carbohydrates, we showed in a previous study that a chronic gavage with HoP‐DM and HHP‐DM differentially modulates the velocity of intestinal contractions and glucose metabolism in adult mice 27 . Indeed, we found that HHP‐DM significantly reduced the amplitude of intestinal contractions in the duodenum and ileum which absorbed large amounts of glucose, but also that HHP‐DM mice displayed an improve glucose tolerance through the modulation of the gut–brain axis activity 27 .…”
Section: Discussionmentioning
confidence: 68%
“…For example, as BSSL remains active in HHP‐DM, 10 we can postulate that milk triacylglycerols and diacylglycerols can be hydrolyzed and absorbed faster and more efficiently metabolized in HHP‐DM pups. For carbohydrates, we showed in a previous study that a chronic gavage with HoP‐DM and HHP‐DM differentially modulates the velocity of intestinal contractions and glucose metabolism in adult mice 27 . Indeed, we found that HHP‐DM significantly reduced the amplitude of intestinal contractions in the duodenum and ileum which absorbed large amounts of glucose, but also that HHP‐DM mice displayed an improve glucose tolerance through the modulation of the gut–brain axis activity 27 .…”
Section: Discussionmentioning
confidence: 68%
“…A growing number of experiments are being conducted to investigate the effect of HPP-treated HM on metabolism and physiology ( Table 6 ). An increase in the expression of antioxidant genes (catalase and super dismutase) and in glucose tolerance was observed in mice fed with HPP-donor milk, as demonstrated by Wemelle et al ( 55 ). Authors also showed a decrease in inflammation markers (F4/80, TNF-α) in these animals.…”
Section: High Pressure Processing (Hpp)mentioning
confidence: 58%
“…Concerning HPP, research so far has been able to show that this methodology would ensure comparable or even improved safety of human milk compared to HoP: most bacteria currently present in human milk, including the vegetative forms of Bacillus cereus , are destroyed by HPP (provided the results will be confirmed in further studies), and antimicrobial activity of HM is preserved. In addition, HPP allows better preservation of nutrients and bioactive components in comparison to HoP ( 24 , 42 , 43 , 48 , 50 , 53 , 55 ). However, the fact that several methodological approaches are used makes extremely difficult to compare studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the impact of HHP-DM on Nfe2l2 mRNA expression, one can speculate that the positive impact observed could be due to one (or more) milk components. In fact, we have recently published that the concentration of GLP-1 is increased in HHP milk compared to HoP milk [ 29 ]. It is well established that GLP-1 signaling could activate Nfe2l2 mRNA expression [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%